On Pointwise Lacunary Statistical Convergence of Order ? of Sequences of Function - Et, Mikail; Sengul, Hacer (Natl Acad Sciences India, 2015)
In this paper we introduce the concepts of pointwise lacunary statistical convergence of order alpha and pointwise w(p)(f, theta)-summability of order alpha of sequences of real valued functions. Also some relations between pointwise S-theta(f)(f)-statistical convergence and pointwise w(p)(alpha)(f, theta)-summability are given.
Keywords: Statistical convergence; Sequences of function; Cesaro summability